Phytoestrogens of Pachyrhizus erosus prevent Bone Loss in an Ovariectomized Rat Model of Osteoporosis - Arief Nurrochmad; Fransiska Leviana; Caecilia Govita Wulancarsari; Endang Lukitaningsih (International Journal of Phytomedicine, 2010)
The effects of the etyl acetate extract of root of Pachyrhizus erosus (L) Urb (EPE) on bone loss and in ovariectomized (ovx) rats model of osteoporosis were investigated. Forty-two 6-weeksold female Sprague–Dawley rats were randomly assigned to six groups as followed, sham-operated, OVX, OVX-Estradiol (2 μg/day), OVX-EPE 200 mg/kg BW, OVX-EPE 400 mg/kg BW, OVX-EPE 800 mg/kg BW for 4 weeks. The administration of EPE was given orally using a stomach tube. The results demonstrated that the administration EPE 200, 400, and 800 mg/kg BW significantly prevented bone loss in OVX rats which these effect equivalent to estradiol. These effects were described in increased length of femur and tibiae, bone density, and mineral content of calcium and phosphorous in bone ash. EPE also significantly prevented OVX-induced uterine atrophy and increased in body weight gain. The femur mechanical testing significantly increased the ultimate load and stiffness of femurs of ovariectomized-rats that its effect was greater than OVX or shamoperated rats. Increased bone density may lead to enhanced bone strength, reducing the risk of fracture, which is evident in the administration of EPE due to high content of mineral density and content and increase the ultimate load. This effect seems to be pro-estrogenic compound, which suppress bone resorption by directly acting on estrogen receptor in bone sites. This study suggest that phytoestrogen compound from Pachyrhizus erosus may offer a potential alternative therapy for the treatment of health problems such as osteoporosis in post-menopausal women.